Study on Diversity of Rodents (Mammalia : Rodentia) in and around Achalpur City, District Amravati, Maharashtra, India - Ahsan, Mohammad Misbahul (International Journal of Scientific Research in Biological Sciences, 2022)
The present study on rodent diversity was done during 2019-2020 for one year by visiting different habitats of Achalpur City, Amravati district of Maharashtra state, India. Total 07 species of rodents under 04 genera of 02 families were recorded from the study area. Human habits, crop field, gardens and ground areas were chosen for sampling of terrestrial rodents, while forest area around the city was selected for arboreal species. Arboreal rodents were observed with the help of binoculars, whereas the standard size live traps were used for trapping of the small and medium size rodents.